Gene expression variation in African and European populations of Drosophila melanogaster. - Hutter, S.; Saminadin-Peter, S.S.; Stephan, W.; Parsch, J. (Genome Biology, 2008)
Differences in levels of gene expression among individuals are an important source of phenotypic variation within populations. Recent microarray studies have revealed that expression variation is abundant in many species, including Drosophila melanogaster. However, previous expression surveys in this species generally focused on a small number of laboratory strains established from derived populations. Thus, these studies were not ideal for population genetic analyses.We surveyed gene expression variation in adult males of 16 D. melanogaster strains from two natural populations, including an ancestral African population and a derived European population. Levels of expression polymorphism were nearly equal in the two populations, but a higher number of differences was detected when comparing strains between populations. Expression variation was greatest for genes associated with few molecular functions or biological processes, as well as those expressed predominantly in males. Our analysis also identified genes that differed in expression level between the European and African populations, which may be candidates for adaptive regulatory evolution. Genes involved in flight musculature and fatty acid metabolism were over-represented in the list of candidates.Overall, stabilizing selection appears to be the major force governing gene expression variation within populations. However, positive selection may be responsible for much of the between-population expression divergence. The nature of the genes identified to differ in expression between populations may reveal which traits were important for local adaptation to the European and African environments.